Molecular subtypes of intrahepatic cholangiocarcinoma - De Santis, Alessandro; Zhu, Lei; Tao, Jianxin; Reißfelder, Christoph; Schölch, Sebastian (Trends in molecular medicine, 2025)
Intrahepatic cholangiocarcinoma (iCCA) presents in two clinically distinct subtypes: large duct (LD-iCCA) and small duct (SD-iCCA). These subtypes exhibit significant molecular, genetic, and histopathological differences that impact patient prognosis and treatment responsiveness. This review advocates for a subtype-specific approach to iCCA research and clinical management, including tailored therapeutic strategies that consider distinct genetic profiles and tumor microenvironments. Current therapeutic approaches hold promise, yet efficacy varies by subtype. Additionally, subtype-specific molecular diagnostics, including DNA methylation-based classifiers and transcriptomic sequencing, have shown potential in refining iCCA subclassification, thereby guiding precision medicine efforts. This article outlines existing clinical trials, key research trajectories, and future directions for developing more effective subtype-adapted therapies for iCCA.
Online verfügbar: 15. Februar 2025, Artikelversion: 13. August 2025
Gesehen am 01.12.2025